ANALISIS KINERJA PEGAWAI DITINJAU DARI FAKTOR INTERNAL DAN EKSTERNAL DI KANTOR URUSAN AGAMA (KUA) KECAMATAN BENJENG KABUPATEN GRESIK JAWA TIMUR - Yuniar, Rizka; Halima, Nur (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
This research aims to analyze employee performance in terms of internal and external factors as well as supporting and inhibiting factors in improving employee performance in KUA Benjeng District, Gresik Regency using a descriptive qualitative analysis approach. The results of the research are that performance is viewed from internal employee factors, work quality is in accordance with the law or SOP and punctuality is optimal. Then employees have various innovations to make it easier to complete work and employees are able to carry out their work in accordance with their main duties and functions. Performance is reviewed from external factors, employees communicate well with superiors and co-workers, employees implement teamwork and employees implement organizational culture well. Supporters in improving employee performance, the quality of their human resources is very responsible for the tasks that have been assigned, employees have competencies that are in accordance with their main duties and functions and work commitment has been implemented well. The obstacles to improving employee performance are inadequate work facilities, employees do not mix family problems into the office and human resources at KUA do not understand technology.